Dampak Limbah Industri Tahu terhadap Kualitas Lingkungan - Kamsul; Sukarjo; Silvia Azka Shalsabila; Fidya Irsya; Ida Rusdiana; Winda Fajriani (PT Pustaka Cendekia Publisher, 2025)
The tofu industry produces liquid waste with BOD, COD, TSS, and pH levels that exceed environmental quality standards, potentially polluting water bodies and causing ecological disturbances. The method used in this study was a Systematic Literature Review sourced from the Google Scholar database via the Publish or Perish and Mendeley applications. Based on the results, it was found that poor waste management reduces the physical, chemical, and biological quality of water, as well as disrupting the health of the surrounding community. Additionally, the lack of awareness among industrial actors and weak enforcement of regulations exacerbate pollution. The implementation of simple waste treatment technologies and strengthened environmental laws are needed as mitigation efforts.